The sufficiency of existed protected areas in conserving the habitat of proboscis monkey (Nasalis larvatus) - WARDATUTTHOYYIBAH WARDATUTTHOYYIBAH; SATYAWAN PUDYATMOKO; SENA ADI SUBRATA; MUHAMMAD ALI IMRON (Society for Indonesian Biodiversity, 2019)
Wardatutthoyyibah, Pudyatmoko S, Subrata SA, Imron MA. 2019. The sufficiency of existed protected areas in conserving the habitat of proboscis monkey (Nasalis larvatus). Biodiversitas 20: 1-10. Proboscis monkey (Nasalis larvatus) is an endemic species on the island of Borneo. Their population size progressively decreased because they are very sensitive to any habitat destruction and human activity. The population of proboscis monkey in 2008 was estimated at only approximately 25,000 in total, of which only 5,000 within the conservation areas. However so, the continuation of habitat degradation is hardly prevented in non-protected areas. To solve the problem, the Indonesian government commits to increase the population of the proboscis monkey, particularly outside the protected areas. To support this goal, the distribution data of N. larvatus for conservation planning has become necessary. This study aims to build predictive models of the N. larvatus in Kalimantan and to measure how big the overlap between the habitat and the land use activity (protected areas, concession areas, plantation, and agriculture areas). The study used the Species Distribution Modelling (SDM) approach and Maximum Entropy (MaxEnt) software. We collected recent data from N. larvatus and a number of environmental variables. The result shows that only 5% of the total of Kalimantan area is suitable for their habitat. The overlap between N. larvatus distribution, land use, and land cover map reveals that only 9% of the distribution lies in protected areas, while 37% lies in concession areas and 27% lies in agriculture and plantations areas. We discuss the spatial distribution of the model and current situation of the land use policy in Kalimantan to provide scientific guidance for the Indonesian government to make a master plan for conserving endangered species N. larvatus.